Spontaneous external auditory canal cholesteatoma in a young male: Imaging findings and differential diagnoses - Aswani, Yashant; Varma, Ravi; Achuthan, Gayathri (Indian Journal of Radiology and Imaging, 2016)
A cholesteatoma is a non-neoplastic lesion of the petrous temporal bone commonly described as “skin in the wrong place.” It typically arises within the middle ear cavity, may drain externally via tympanic membrane (mural type), or may originate in the external auditory canal (EAC). The latter type is rarely encountered and typically affects the elderly. EAC cholesteatoma poses diagnostic challenges because it has numerous differential diagnoses. The present case describes a 19-year-old male who presented with gradually progressive diminution of hearing in a previously naïve right ear since 8 months. A soft tissue attenuation lesion confined to the right EAC with erosion of the canal on computed tomography prompted magnetic resonance imaging (MRI). The lesion showed restricted diffusion on MRI. Thus, a diagnosis of spontaneous EAC cholesteatoma was established. The case elucidates the rarity of spontaneous EAC cholesteatoma in a young male. In addition, it describes the role of imaging to detect, delineate the extent, and characterize lesions of petrous temporal bone. The case also discusses common differential diagnoses of EAC cholesteatoma, as well as the importance of diffusion weighted imaging in EAC cholesteatoma similar to its middle ear counterpart.
Keywords: Cholesteatoma; CT scan; diffusion weighted MRI; external auditory canal